PENGUAT KELAS D DENGAN METODE SUMMING INTEGRATOR - Murtianta, Budihardja (Elektrika, 2019)
A class D amplifier is one in which the output transistors are operated as switches. When a transistor is off, the current through it is zero and when it is on, the voltage across it is small, ideally zero. Thus the power dissipation is very low, so it requires a smaller heat sink for the amplifier. Class D amplifier operation is based on analog principles and there is no digital encoding of the signal. Before the emergence of class D amplifiers, the standard classes were class A, class AB, class B, and class C. The classic method for generating signals driving a transistor MOSFET is to use a comparator. One input is driven by an incoming audio signal, and the other by a triangle wave or a sawtooth wave at the required switching frequency. The frequency of a triangular or sawtooth wave must be higher than the audio input. MOSFET transistors work in a complementary manner that operates as a switch. Triangle waves are usually generated by square waves fed to the integrator circuit. So the main part of processing audio signals into PWM (Pulse Width Modulation) is the integrator and comparator. In this paper, we will discuss the work of a class D amplifier system using the summing integrator method as its main part.